2011
DOI: 10.1007/s00404-011-2081-9
|View full text |Cite
|
Sign up to set email alerts
|

Chagas disease in Latin American pregnant immigrants: experience in a non-endemic country

Abstract: Seroprevalence of T. cruzi infection in Latin American pregnant women coming from Bolivia and Paraguay is high. Those women should be screened for T. cruzi to control mother-to-child transmission in non-endemic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
3
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 18 publications
(19 reference statements)
1
12
3
7
Order By: Relevance
“…Within Spain, 7 of the 12 studies with prevalence estimates of Chagas disease in migrants were similar to the highest countrywide estimate (Del Pino and Coll, 2006; Giménez-Martí et al, 2006; Munoz-Vilches et al, 2012; Paricio-Talayero et al, 2008; Roca et al, 2011; Santiago et al, 2012; Soriano Arandes et al, 2009), two were lower(Piron et al, 2008; Ramos et al, 2012a), and three(Avila Arzanegui et al, 2013; Barona-Vilar et al, 2012; Lucas and Barba, 2009) were higher (Figure 2). One additional study was conducted in Spain, but its results are not summarized here because it was a non-representative sample of only Bolivian and Paraguayan participants (Ramos et al, 2012b).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Within Spain, 7 of the 12 studies with prevalence estimates of Chagas disease in migrants were similar to the highest countrywide estimate (Del Pino and Coll, 2006; Giménez-Martí et al, 2006; Munoz-Vilches et al, 2012; Paricio-Talayero et al, 2008; Roca et al, 2011; Santiago et al, 2012; Soriano Arandes et al, 2009), two were lower(Piron et al, 2008; Ramos et al, 2012a), and three(Avila Arzanegui et al, 2013; Barona-Vilar et al, 2012; Lucas and Barba, 2009) were higher (Figure 2). One additional study was conducted in Spain, but its results are not summarized here because it was a non-representative sample of only Bolivian and Paraguayan participants (Ramos et al, 2012b).…”
Section: Resultssupporting
confidence: 57%
“…Of these studies, 11 reported higher prevalence estimates as compared to PAHO (Barona-Vilar et al, 2012; Jackson et al, 2010; Jackson et al, 2009; Lucas and Barba, 2009; Paricio-Talayero et al, 2008; Roca et al, 2011) and 6 had similar estimates (El Ghouzzi et al, 2010; Ramos et al, 2012a; Ramos et al, 2012b). For Paraguayan migrants, 3 studies had similar prevalence estimates to countrywide estimates (Ramos et al, 2012a; Ramos et al, 2012b), while 3 were higher (Figure 4) (Avila Arzanegui et al, 2013; Barona-Vilar et al, 2012; Lucas and Barba, 2009). However, it should be noted that one sample that was higher was only based on 6 individuals, and thus was very imprecise (95% CI: 3.0–56.4) (Lucas and Barba, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the child-bearing age women (10–49 years) analyzed in the present study, the described prevalence of 6.1% [27] was higher than that described by Munhoz et al [13] but lower than those registered in Europe (Tables 1 and 2) [10,11,12,14,17,23,24]. Moreover, in recent and previous publications, a higher prevalence was registered for general Bolivian immigrants in European countries [5,12, Table 1] compared with São Paulo [27].…”
Section: Discussioncontrasting
confidence: 65%
“…Cancino 2015 [32] Frank 1997 [24] Paricio-Talayero 2008 [43] Angheben 2011 [23] Martínez 2009 [38] Angheben 2011 [23] Roca 2011 [9] Ramos 2012 [29] Study Perez-Ayala 2010 [6] Angheben 2011 [23] Soriano 2009 [31] Avila Arzanegui 2013 [36] Barona-Vilar 2012 [37] O'Brien 2013 [35] Perez-Molina 2011 [28] Otero…”
Section: Muñoz-vilches 2012 [40]mentioning
confidence: 99%